2015
DOI: 10.1093/cercor/bhv233
|View full text |Cite
|
Sign up to set email alerts
|

Community Socioeconomic Disadvantage in Midlife Relates to Cortical Morphology via Neuroendocrine and Cardiometabolic Pathways

Abstract: Residing in communities of socioeconomic disadvantage confers risk for chronic diseases and cognitive aging, as well as risk for biological factors that negatively affect brain morphology. The present study tested whether community disadvantage negatively associates with brain morphology via 2 biological factors encompassing cardiometabolic disease risk and neuroendocrine function. Participants were 448 midlife adults aged 30-54 years (236 women) who underwent structural neuroimaging to assess cortical and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 91 publications
12
87
1
1
Order By: Relevance
“…Previous studies have demonstrated a link between obesity and reduced cortical thickness, an association suspected to be mediated by low grade inflammation (Veit et al, 2014). Other evidence suggests that relative socioeconomic disadvantage is associated with alterations in cortical morphology that are mediated by greater inflammation (Gianaros et al, 2015; Krishnadas et al, 2013). Indices of allostatic load, which incorporate measures of both adiposity and inflammation, may thus have utility as an integrative marker of risk factors for changes in brain morphology in aging and stress-related illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a link between obesity and reduced cortical thickness, an association suspected to be mediated by low grade inflammation (Veit et al, 2014). Other evidence suggests that relative socioeconomic disadvantage is associated with alterations in cortical morphology that are mediated by greater inflammation (Gianaros et al, 2015; Krishnadas et al, 2013). Indices of allostatic load, which incorporate measures of both adiposity and inflammation, may thus have utility as an integrative marker of risk factors for changes in brain morphology in aging and stress-related illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Neither SES nor EduYears-PGS were significantly related to average cortical thickness at age 14 or to the thinning over adolescence. Furthermore, there were no significant regional associations (at 14 or from [14][15][16][17][18][19] for cortical thickness from either SES or EduYears-PGS, regardless of global correction.…”
Section: Cortical Thicknessmentioning
confidence: 80%
“…The distinction is important because it tells us about the potential mechanisms in play, has functional consequences for the individual and could have implications for remedial interventions. Therefore, we tested for distinct global and regional associations -a practice still ignored in the literature 4,5,8 , with the exception of only one known study to date 16 . The latter, however, did not control for any genetic component of SES.…”
Section: Introductionmentioning
confidence: 99%
“…Our measure of community SED was estimated based on US Census data geocoded to participants’ zip codes. This approach is consistent with the few published studies examining community SED and brain organization (Gianaros et al, ; Krishnadas et al, ). As others have noted, however, there is no best approach for measuring within‐household or community‐level SED (Farah, ; Ursache & Noble, ).…”
Section: Discussionmentioning
confidence: 99%